(untitled) (Journal of the Bangladesh Agricultural University, 2020)
This research work was carried out to determine the optimum quantity of jackfruit seeds powder to substitute skimmed milk powder (SMP) for yoghurt preparation. Total six yoghurt samples were prepared where one is control (A) and rest five samples were prepared by mixing different ratios of jackfruit seeds powder and SMP. 0%, 0.75%, 1.5%, 2.25% and 3% of jackfruit seeds powder were mixed with 3%, 2.25%, 1.5%. 0.75% and 0% SMP and designated as B, C, D, E and F respectively. Physical, chemical and microbiological and cost analysis of prepared samples were done. Yoghurt sample (D) showed highest score in total physical test but individual score for body and consistency of sample F is maximum. Solubility % of jackfruit seeds powder were found 10.96. Highest acidity level was found in control yoghurt and highest pH in sample F. Maximum fat content (g/kg) was found in sample F, but utmost protein content was found in sample (B). Total solids, ash and carbohydrate content of sample F were significantly higher (p<0.01) than all other yoghurt samples and control sample showed the lowest content. Microbiological analysis showed total viable count (cfu/g) of control sample (A) is significantly higher (p<0.01) but no significant variation (p>0.05) was found in coliform count (cfu/g). Yeast and mold count of sample F is significantly higher (p<0.01) than all other samples while control sample showed minimal count. Cost analysis showed substitution of jackfruit seeds powder with SMP sharply reduced the production cost. Considering all parameters, it can be concluded that, sample F showed highest content in chemical analysis but this yoghurt samples organoleptic acceptance and microbiological quality is worst. Overall, sample (D) proclaimed best moreover, physical acceptance of this sample is significantly higher (p <0.01) than all other yoghurt samples. J Bangladesh Agril Univ 18(3): 636–642, 2020 https://doi.org/10.5455/JBAU.104981